The effect of Momordica charantia intake on the estrogen receptors ESR alpha/ESR beta gene levels and apoptosis on uterine tissue in ovariectomy rats - YOLDEMİR, AHMET TEVFİK; KAYA, ÖZLEM TUĞÇE; OBA, RABİA; ÇETİNEL, ŞULE; ÖZDEMİR KUMRAL, ZARİFE NİGAR (SPRINGER, 2015)
Estrogen or combinational hormone therapy can protect to menopausal symptoms but exogenous estrogen therapy has some potential risks which in turns lead to the appearance of various diseases. In recent years plants with high phytoestrogen content are recommended as therapeutic agents for postmenopausal hormonal treatment. In this research, we investigated the effects of Momordica charantia (MC) on the estrogen production and E2 as well as anti-oxidative and anti-apoptotic role on the ovariectomy rat model. The rats were ovariectomized and fed on 2 g/kg of fruit extra of MC for 30 days by gavage. 17-beta estradiol (E2) and 8-OHdG levels in serum, markers of oxidative damage of ROS and ESR alpha, ESR beta and NF-kB gene levels were measured in uterus horn tissue. Caspase-3, caspase-9, TNF-alpha, IL-6, IL-10, Bcl-2 and Nf-kB proteins expression were assessed by western blotting. Structural changes in tissue were examined with H&E staining. MC administration also stimulated the E2 production and ESR alpha/ESR beta gene levels and the inhibited oxidative damage. Furthermore, MC treatment enhanced anti-apoptotic and anti-inflammatory process and tissue regeneration. Data herein support that MC directly regulates uterine estrogen response and may serve as a new phytoestrogenic substance for the treatment of post-menopausal symptoms.
Keywords: Momordica charantia; Overectomy; 17-beta Estradiol; Estrogen receptors; Oxidative DNA damage; Apoptosis; OXIDATIVE DAMAGE; ER-ALPHA; ANTIOXIDANT; MECHANISMS; EXTRACT; PREVENTION; PHYTOESTROGENS; PROGESTERONE; EXPRESSION; LEIOMYOMA